Pengaruh Kualitas Sumber Daya Manusia, Profesionalisme Kerja, dan Komitmen Berkelanjutan Terhadap Kinerja Karyawan Pemanen Kelapa Sawit PT. Bangun Nusa Mandiri di Kabupaten Ketapang - Ronaldo, Ronaldo; Kurniati, Dewi; Oktoriana, Shenny (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
This study aims to analyze the influence of human resource quality, work professionalism, and continuous commitment on the performance of oil palm harvester employees at PT. Bangun Nusa Mandiri, Ketapang Regency. The research method used is a quantitative approach, with primary data collection through a questionnaire distributed to 100 employees. The data obtained was analyzed using the Structural Equation Modeling (SEM) analysis technique with SmartPLS Version 3.0 software to test the hypothesis that had been formulated. The results of the study show that the quality of human resources, work professionalism, and continuous commitment have a positive and significant influence on employee performance. This finding is expected to contribute to the company in improving the quality of human resources and employee work professionalism in order to achieve better organizational goals